Sosialisasi Peran Informatika Medis Dalam Transformasi Teknologi Kesehatan - Suryani; Vicky Arfeni Warongan; Alesia Lorenzza Sinaga; Sofyan Pariyasto; Syahra Eliza Yanti; Maya Marshella br Ginting (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The rapid development of digital technology has brought significant changes in the healthcare system, notably through the integration of health informatics. However, awareness and understanding of this field among high school students remain limited. This community service project aimed to promote digital health literacy by introducing health informatics to students at Madrasah Aliyah Al Manar Medan. Using an educational-participatory approach, the activities involved interactive presentations, group discussions, and hands-on simulations of digital health applications. The results indicated a substantial increase in students' knowledge and interest in health technology, with many demonstrating enthusiasm for future careers in health informatics. The program also fostered critical awareness regarding the use of technology in healthcare, highlighting the role of young people in supporting digital transformation in health services. Furthermore, the emergence of active student facilitators during the simulation sessions illustrates the development of local leadership potential. These findings suggest that early digital health education using participatory methods can be an effective strategy to nurture digital competence and social responsibility among youth.